2009
DOI: 10.1007/s11270-009-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 137Cs and 239,240Pu Distribution in Forest Soils of the Opole Anomaly

Abstract: Distribution of 137 Cs and 239,240 Pu in the forest soils horizons of the Opole Anomaly was established. Gamma and alpha spectrometry was used for determination of these isotopes. It was found that the 137 Cs activity was approx. 1,000 times higher than that of 239,240 Pu. The highest activities of both radioisotopes were found close to the boundary region in soil profile where the organic horizon turns into the inorganic one. Cluster analysis did not clearly indicate the group's existence in data in respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In this way, it was possible, for example, to measure the concentration of 90 Sr, 239+240 Pu, and beta-emitting 241 Pu in subsequent layers of the soil profiles. This enabled us to calculate a vertical migration rate of the isotopes [ 46 , 48 52 ].…”
Section: Radiotracer and Radiochemical Researchesmentioning
confidence: 99%
“…In this way, it was possible, for example, to measure the concentration of 90 Sr, 239+240 Pu, and beta-emitting 241 Pu in subsequent layers of the soil profiles. This enabled us to calculate a vertical migration rate of the isotopes [ 46 , 48 52 ].…”
Section: Radiotracer and Radiochemical Researchesmentioning
confidence: 99%
“…Studies on determination of radioisotope concentration level in soils of Lublin region were started in 1996 [ 5 ] and continued in 1999 [ 6 ]. Particularly, a vertical transport of different radionuclides in soil [ 6 , 7 ], their binding with the soil fractions with different physicochemical properties using sequential extraction [ 8 ], transfer to plants [ 9 ] and animals [ 10 ] has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that approximately 90 % of 137 Cs is stored in the top 10 cm of soil (e.g. Takenaka et al 1998;Beli et al 1994;Ziembik et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This study, similar to other studies that have documented translocation of 137 Cs from soil to higher plants (Tagami et al 2012;Lukšienė et al 2013), demonstrates that there may be local dispersion of 137 Cs accumulated in soil. 137 Cs in the environment is tied up mainly in topsoil, and its circulation is limited to genetic levels O-A, from which it is integrated into the plant structure via the root system, creating a new sub-level Ol over time (Ziembik et al 2010;Dołhańczuk-Śródka et al 2006;Dołhańczuk-Śródka and Wacławek 2007). Such local dispersion can be illustrated by wider zones, limited by isolines, created by comparing the results from studies carried out in 2007 and 2010 (Fig.…”
Section: Discussionmentioning
confidence: 99%